Composite member, golf club, fishing rod, flying object

By integrating a glass-based coating film with dispersed filler particles onto a lightweight substrate, the composite member addresses the issue of reduced Young's modulus and increased vibrations in golf clubs, fishing rods, and flying objects, resulting in improved stability and performance.

JP2025047379APending Publication Date: 2025-04-03HARDOLASS HLDG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023155838
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-04-03

AI Technical Summary

Technical Problem

Existing composite members, such as golf clubs, fishing rods, and flying objects, suffer from reduced Young's modulus, leading to increased vibrations and instability during high-speed movement, which affects performance and accuracy.

Method used

A composite member comprising a lightweight substrate with a glass-based coating film, where a plurality of filler particles are dispersed and mixed inside the coating film, improving the Young's modulus and reducing vibrations during high-speed movement.

Benefits of technology

The proposed solution enhances the Young's modulus of the lightweight substrate, suppressing vibrations and improving stability during high-speed movement, thereby increasing propulsion force and reducing noise in golf clubs, fishing rods, and flying objects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025047379000001_ABST
    Figure 2025047379000001_ABST
Patent Text Reader

Abstract

To provide a composite member capable of improving Young's modulus (hardness), suppressing occurrence of vibration during high-speed movement, and improving stability during high-speed movement.SOLUTION: A composite member 11 comprises: an elastically deformable lightweight base material 12 that is any one of CFRP, FRP, ABS resin, polycarbonate, carbon fiber polycarbonate, aluminum alloy (Al alloy), and magnesium alloy (Mg alloy); and a glass-based coating film 10 formed on a lightweight base material 12 and having a plurality of filler particles 15 dispersed therein. A density of the lightweight base material 12 is 3.0 g / cm3 or less, and a value obtained by dividing a value of Young's modulus (GPa) of filler particles 15 by a density (g / cm3) of the filler particles 15 is 30 or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite member, a golf club, a fishing rod, and a flying object. [Background technology]

[0002] A golf club has been disclosed in which at least the outer surface of the shaft portion on the club head side of the golf club is covered almost entirely with a coating material having dimples on its surface layer consisting of nano-level minute irregularities. (See Patent Document 1.) With this golf club, air near the club head side of the shaft portion that moves at high speed as the golf club swings is easily captured by the dimples consisting of nano-level irregularities in the coating material that covers the outer surface of the shaft portion, and the airflow near the shaft portion generated by the swing maintains its laminar state for a long time, delaying the occurrence of a turbulent state, thereby reducing the air resistance imposed on the golf club.

[0003] Also, a coating liquid is disclosed that contains 20-60wt% of organic polysilazane, 5-15wt% of alkyl silicate condensate, and 0-80wt% of organic solvent, and the content of methyl groups in the organic polysilazane is 50% or more (see Patent Document 2). In this coating liquid, the organic polysilazane reacts with moisture to form a coating layer of an inorganic-organic composite structure in which an organic functional group is linked as a side chain to a part of the main chain by siloxane bond, and the alkyl silicate condensate acts as a crosslinking agent to form a crosslinked structure in the coating layer, thereby reducing the elastic modulus of the glass coating film and maintaining flexibility even when the film thickness is more than a certain level. Therefore, the glass coating film can follow the deformation of the article to be coated, the occurrence of cracks and peeling is prevented, and impact resistance and corrosion resistance can be ensured. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-51291 A [Patent Document 2] JP 2021-14514 A Summary of the Invention [Problem to be solved by the invention]

[0005] Golf clubs with carbon shafts are made for senior golfers and female golfers who lack power. As for drivers and fairway woods, carbon shafts are used in almost all models. Carbon shafts are light, weighing 50 to 80 grams, and are easy to swing firmly even without power. The shaft has a large flexibility and torque (ease of twisting), making it easier to hit the ball high and increasing the flight distance. On the other hand, the shaft is prone to vibration due to air resistance during the swing, and the vibration of the shaft causes the club head to shake, and when the ball impacts, the club head face becomes a hook face or an open face, making the ball prone to curving left and right.

[0006] When the glass coating film made from the coating liquid disclosed in Patent Document 2 is formed on an elastically deformable lightweight substrate, the Young's modulus of the lightweight substrate cannot be improved. Even if air resistance acts on a composite member consisting of a lightweight substrate and a glass coating film during high-speed movement, the generation of vibrations in the composite member during high-speed movement cannot be suppressed, and the stability of the composite member during high-speed movement cannot be improved.

[0007] Even if a glass coating film made from the coating liquid disclosed in Patent Document 2 is formed on a fishing rod, the Young's modulus of the rod cannot be increased, the vibration of the rod during casting cannot be suppressed, and the casting accuracy cannot be improved. Also, even if a glass coating film made from the coating liquid disclosed in Patent Document 2 is formed on the propeller of a flying object, the Young's modulus of the propeller cannot be increased, and the occurrence of vibration in the propeller during flight cannot be suppressed. Therefore, the flying speed of the flying object cannot be increased, and the stability during flight and hovering cannot be improved.

[0008] An object of the present invention is to provide a composite member capable of improving Young's modulus (hardness), suppressing the occurrence of vibration during high-speed movement, and improving stability during high-speed movement. Another object of the present invention is to provide a golf club capable of suppressing shaft vibration during swinging while having stable distance performance, suppressing club head wobble, and stabilizing the flight direction of the ball. Another object of the present invention is to provide a fishing rod capable of suppressing rod vibration during casting, thereby improving casting accuracy. Another object of the present invention is to provide a flying object capable of suppressing the occurrence of vibration in a propeller during flight, increasing flight speed, and improving stability during flight and hovering. [Means for solving the problem]

[0009] The composite member of the present invention for solving the above problems comprises an elastically deformable lightweight substrate and a glass-based coating film formed on the lightweight substrate and having a plurality of filler particles dispersed therein, the density of the lightweight substrate being 3.0 g / cm 3 The Young's modulus (GPa) of the filler particles is expressed as the density (g / cm 3 ) is 30 or more.

[0010] In one example of the composite member of the present invention, the lightweight base material is any one of CFRP, FRP, ABS resin, polycarbonate, carbon fiber polycarbonate, aluminum alloy (Al alloy), and magnesium alloy (Mg alloy).

[0011] In another example of the composite material of the present invention, the average thickness of the glass-based coating film is 0.5 μm or more and 20 μm or less.

[0012] In another example of the composite member of the present invention, the filler particles are at least one of Si, SiO2, Al2O3, ZrO2, AlN, Si3N4, and SiC.

[0013] In another example of the composite member of the present invention, the filler particles have a plate-like shape.

[0014] Another example of the composite member of the present invention is a filler particle having an average particle size D 50 However, it is greater than or equal to 0.1 μm and less than or equal to 20 μm.

[0015] In another example of the composite member of the present invention, the content of the filler particles in the glass-based coating film is 5 to 50 by volume.

[0016] In another example of the composite member of the present invention, the glass-based coating film is either a glass-based inorganic coating film or a glass-based organic / inorganic hybrid coating film.

[0017] Another example of the present invention is a golf club using the composite material in the shaft of the golf club.

[0018] Another example of the present invention is a fishing rod that uses the composite material in the rod.

[0019] Another example of the present invention is a flying object characterized in that a composite material is used for a propeller or rotor. Effect of the Invention

[0020] According to the composite member of the present invention, a glass-based coating film having a plurality of filler particles dispersed therein is formed on an elastically deformable lightweight substrate, and the density of the lightweight substrate is 3.0 g / cm 3 The Young's modulus (GPa) of the filler particles is expressed as the density (g / cm 3 ) is 30 or more, the Young's modulus of the glass-based coating film is improved by the filler particles, and the Young's modulus (hardness) of the lightweight substrate on which the glass-based coating film is formed can be improved. By improving the Young's modulus of the lightweight substrate, the composite member can suppress the generation of vibrations in the composite member during high-speed movement or high-speed rotation, even if a large air resistance acts on the composite member during high-speed movement or high-speed rotation, thereby improving the propulsive force of the composite member and reducing the noise generated during high-speed movement or high-speed rotation of the composite member.

[0021] In a composite member whose lightweight base material is any one of CFRP, FRP, ABS resin, polycarbonate, carbon fiber polycarbonate, aluminum alloy (Al alloy), and magnesium alloy (Mg alloy), a glass-based coating film having a plurality of filler particles dispersed therein is formed on the lightweight base material which is any one of CFRP, FRP, ABS resin, polycarbonate, carbon fiber polycarbonate, aluminum alloy (Al alloy), and magnesium alloy (Mg alloy). Therefore, the Young's modulus (hardness) of the CFRP, FRP, ABS resin, polycarbonate, carbon fiber polycarbonate, aluminum alloy (Al alloy), and magnesium alloy (Mg alloy) can be improved by the glass-based coating film having a plurality of filler particles dispersed therein. By improving the Young's modulus (hardness) of the lightweight base material, composite materials can suppress the generation of vibrations in the composite material during high-speed movement or rotation, even if a large amount of air resistance acts on the CFRP, FRP, ABS resin, polycarbonate, carbon fiber polycarbonate, aluminum alloy (Al alloy), or magnesium alloy (Mg alloy) that makes up the composite material during high-speed movement or rotation.This can improve the propulsive force of the composite material and reduce the noise generated when the composite material moves or rotates at high speed.

[0022] In a composite member having a glass-based coating film with an average thickness of 0.5 μm or more and 20 μm or less, even if a glass-based coating film with the average thickness is formed on a lightweight substrate, the weight of the lightweight substrate does not change significantly, and the weight of the composite member can be maintained as light. Since the glass-based coating film with the average thickness and a plurality of filler particles dispersed therein is formed on the lightweight substrate in the composite member, the Young's modulus (hardness) of the lightweight substrate can be improved by the glass-based coating film with a plurality of filler particles dispersed therein. Since the Young's modulus (hardness) of the lightweight substrate is improved, even if a large air resistance acts on the composite member on which the glass-based coating film with the average thickness is formed during high-speed movement or high-speed rotation, the generation of vibration in the composite member during high-speed movement or high-speed rotation can be suppressed, and the propulsive force of the composite member can be improved, and the noise generated during high-speed movement or high-speed rotation of the composite member can be reduced.

[0023] In a composite member in which the filler particles are at least one of Si, SiO2, Al2O3, ZrO2, AlN, Si3N4, and SiC, the filler particles, which are at least one of Si, SiO2, Al2O3, ZrO2, AlN, Si3N4, and SiC, are dispersed and mixed inside the glass-based coating film, thereby improving the Young's modulus of the glass-based coating film and improving the Young's modulus (hardness) of the lightweight substrate on which the glass-based coating film is formed. In the composite member, the Young's modulus (hardness) of the lightweight substrate is improved, so that even if a large air resistance acts on the composite member on which the glass-based coating film in which the filler particles are dispersed and mixed is formed during high-speed movement or high-speed rotation, the generation of vibration in the composite member during high-speed movement or high-speed rotation can be suppressed, and the propulsive force of the composite member can be improved, and the noise generated during high-speed movement or high-speed rotation of the composite member can be reduced.

[0024] In a composite member in which the filler particles are plate-shaped, a plurality of plate-shaped filler particles are dispersed and mixed inside the glass-based coating film, thereby improving the Young's modulus of the glass-based coating film and improving the Young's modulus (hardness) of the lightweight substrate on which the glass-based coating film is formed. Even if a large air resistance acts on the composite member on which the glass-based coating film with the plate-shaped filler particles is formed during high-speed movement or high-speed rotation, the composite member can suppress the generation of vibrations in the composite member during high-speed movement or high-speed rotation, thereby improving the propulsive force of the composite member and reducing the noise generated during high-speed movement or high-speed rotation of the composite member.

[0025] Average particle size of filler particles D 50 The composite material having an average particle size D of the filler particles is 0.1 μm or more and 20 μm or less. 50 Since the average particle diameter D is within the above range, the filler particles can be dispersed and mixed evenly throughout the entire area of ​​the glass-based coating film, and the Young's modulus of the glass-based coating film is improved by the filler particles dispersed and mixed throughout the entire area of ​​the glass-based coating film, thereby improving the Young's modulus (hardness) of the lightweight substrate on which the glass-based coating film is formed. 50 Even if a large air resistance acts on a composite material having a glass-based coating film formed thereon having the filler particles dispersed therein when the composite material moves or rotates at high speed, the generation of vibrations in the composite material when the composite material moves or rotates at high speed can be suppressed, the propulsive force of the composite material can be improved, and the noise generated when the composite material moves or rotates at high speed can be reduced.

[0026] In a composite member having a glass-based coating film with a filler particle content of 5 to 50 volumes, the glass-based coating film contains filler particles at the above content, so that the Young's modulus of the glass-based coating film can be reliably improved by the filler particles, and the Young's modulus (hardness) of the lightweight substrate on which the glass-based coating film is formed can be reliably improved. Since the Young's modulus (hardness) of the lightweight substrate is improved, even if a large air resistance acts on the composite member on which the glass-based coating film with the filler particles dispersed and mixed therein is formed, the generation of vibration in the composite member during high-speed movement or high-speed rotation can be suppressed, so that the propulsive force of the composite member can be improved and the noise generated during high-speed movement or high-speed rotation of the composite member can be reduced.

[0027] In a composite member in which the glass-based coating film is either a glass-based inorganic coating film or a glass-based organic / inorganic hybrid coating film, filler particles are dispersed and mixed inside the glass-based inorganic coating film or the glass-based organic / inorganic hybrid coating film, thereby reliably improving the Young's modulus of the glass-based inorganic coating film or the glass-based organic / inorganic hybrid coating film, and reliably improving the Young's modulus (hardness) of the lightweight substrate on which the glass-based inorganic coating film or the glass-based organic / inorganic hybrid coating film is formed. By improving the Young's modulus of the lightweight substrate, the composite member can suppress the generation of vibrations in the composite member during high-speed movement or high-speed rotation even if a large air resistance acts on the composite member during high-speed movement or high-speed rotation, thereby improving the propulsive force of the composite member and reducing the noise generated during high-speed movement or high-speed rotation of the composite member.

[0028] In a golf club using the composite member according to the present invention in its shaft, the Young's modulus of the glass-based coating film is improved by the filler particles, and the Young's modulus (hardness) of the shaft (composite member) on which the glass-based coating film is formed can be increased. Because the Young's modulus of the golf club can be increased, even if a large air resistance acts on the shaft when the golf club is swung, the occurrence of vibration in the shaft during the swing can be suppressed, and the shaking of the club head can be suppressed, and the flight distance of the golf ball can be increased and the flight direction of the ball can be stabilized.

[0029] In a fishing rod using the composite member according to the present invention, the Young's modulus of the glass-based coating film is improved by the filler particles, and the Young's modulus (hardness) of the rod (composite member) on which the glass-based coating film is formed can be increased. Since the Young's modulus of the fishing rod can be increased, even if a large air resistance acts on the rod when casting the fishing rod, the occurrence of vibration in the rod during casting can be suppressed, rod shaking can be suppressed, the accuracy of casting can be improved, and the flight direction of a lure or the like can be stabilized.

[0030] In a flying object using the composite member according to the present invention for its propeller or rotor, the Young's modulus of the glass-based coating film is improved by the filler particles, and the Young's modulus (hardness) of the propeller (composite member) or rotor (composite member) on which the glass-based coating film is formed can be increased. Since the Young's modulus of the propeller or rotor of the flying object can be increased, even if a large air resistance acts on the propeller or rotor during the flight of the flying object using the composite member, the occurrence of vibration in the propeller or rotor during the flight of the flying object can be suppressed, and the propulsive force of the propeller or rotor can be improved. Since the occurrence of vibration in the propeller or rotor of the flying object is suppressed and the propulsive force of the propeller or rotor is improved, the flying speed of the flying object can be increased and the stability of the flying object during flight and hovering can be improved. The flying object can reduce the noise generated from the propeller or rotor during its flight. [Brief description of the drawings]

[0031] [Figure 1] An image of a composite member showing an enlarged view of a glass-based coating film formed on a lightweight substrate. [Diagram 2] This is a cross-sectional view explaining in chronological order the mechanism by which an inorganic glass coating film or an organic / inorganic hybrid glass coating film is formed from a glass-based coating liquid on the surface of a lightweight substrate coated with the coating liquid. [Diagram 3] FIG. 1 is an image diagram showing an example of the structure of an inorganic glass coating film. [Figure 4] An image showing an example of the structure of an organic / inorganic hybrid glass coating film. [Diagram 5] FIG. 1 is a perspective view of a golf club shown as an example. [Figure 6] Cross-sectional view taken along line AA in Figure 5. [Figure 7] Cross-sectional view of line BB in Figure 5. [Figure 8] FIG. 1 is a perspective view of a fishing rod as an example. [Figure 9] Cross-sectional view taken along line CC in Figure 8. [Figure 10] FIG. 1 is a perspective view of a propeller aircraft shown as an example. [Figure 11] Cross-sectional view of line DD in Figure 10. [Figure 12] FIG. 1 is a perspective view of a helicopter as an example. [Figure 13] Cross-sectional view taken along line EE in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] The composite member according to the present invention will be described in detail with reference to the attached drawings. FIG. 1 is an image of a composite member 11 showing an enlarged glass-based coating film 10 formed on a lightweight substrate, and FIG. 2 is a cross-sectional view for explaining in a time series the mechanism by which an inorganic glass coating film 10a or an organic / inorganic hybrid glass coating film 10b is formed from a coating liquid 14 on a surface 13 (front surface, back surface) of a lightweight substrate 12 coated (applied) with the coating liquid 14. FIG. 3 is an image showing an example of the structure of the inorganic glass coating film 10a, and FIG. 4 is an image showing an example of the structure of the organic / inorganic hybrid glass coating film 10b. In FIG. 1, the filler particles 15 dispersed and mixed inside the glass-based coating film 10 are illustrated as an image that can be seen, but in reality, the filler particles 15 cannot be seen with the naked eye.

[0033] The composite material 11 in FIG. 1 is formed of an elastically deformable lightweight substrate 12 and a glass-based coating film 10 formed on the lightweight substrate 12. The composite material 11 is used for a club head 17 and a shaft 18 of a golf club 16, a rod 20 of a fishing rod 19, a propeller 21, and a rotor 22, which will be described later. The glass-based coating film 10 is formed (formed) on a surface 13 (contact surface) of the lightweight substrate 12 forming the composite material 11. Furthermore, the glass-based coating film 10 is formed (formed) on a surface 13 (contact surface 13) of a club head 17 and a shaft 18 of a golf club 16 (composite material 11), and is formed (formed) on a surface 13 (contact surface 13) of a rod 20 of a fishing rod 19 (composite material 11). Also, the glass-based coating film 10 is formed (formed) on a surface 13 (contact surface) of a propeller 21, and is formed (formed) on a surface 13 (contact surface) of a rotor 22.

[0034] The glass-based coating film 10 includes a glass-based inorganic coating film 10a and a glass-based organic / inorganic hybrid coating film 10b. The glass-based coating film 10 is produced by coating (applying) a coating liquid 14 onto a lightweight substrate 12, golf club, fishing rod, propeller, or rotor, which is to be covered (the substrate on which the glass-based coating film 10 is to be formed).

[0035] The coating liquid 14 for making the glass-based coating film 10 is coated (applied) on the surface 13 (contact surface) of the lightweight substrate 12 (article). The hardened coating liquid 14 forms the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) that covers the surface 13 (contact surface) of the lightweight substrate 12. As the raw materials for the coating liquid 14, a liquid organosilicon material (silicon material) consisting of at least one of organic polysilazane (polysilazane) and siloxane, an alkyl silicate condensate, and an inert organic solvent are used. Alternatively, a low molecular weight silane is used. A plurality of filler particles 15 are dispersed and mixed in the coating liquid 14.

[0036] Either one of organic polysilazane (perhydropolysilazane (polymeric silane)) and siloxane (polymeric silane) may be used, or a mixture of both may be used. The coating liquid 14 is produced by mixing and stirring an organic silicon material, an alkyl silicate condensate, and an inert organic solvent in a predetermined blending ratio. In the coating liquid 14, the organic silicon material consisting of at least one of organic polysilazane and siloxane, and the alkyl silicate condensate are diluted with an inert organic solvent.

[0037] Organic polysilazane (perhydropolysilazane) is a polymer having Si-N bonds and functional groups (R1 to R3) and formed from -(SiR1R2-NR3)- units represented by the following general formula (1), in which at least one of the functional groups R1 and R2 directly bonded to Si is an organic polymer formed from an organic functional group such as an alkyl group having carbon (C).

[0038] [ka] The organic polysilazane has a content of 50% or more of methyl group (CH3), which is one of the functional groups (R1 to R3) of an organic compound having a structure in which a carbon atom is replaced by three hydrogen atoms. The organic polysilazane may be not only a polymer formed from one type of -(SiR1R2-NR3)- unit, but also a polymer formed from multiple types of -(SiR1R2-NR3)- units having different compositions of functional groups (R1 to R3). Furthermore, the organic polysilazane may be a polymer having a chain, cyclic or crosslinked structure, or a polymer having a combination of these structures.

[0039] As an example of organic polysilazane, organic polysilazane (A) is a -(SiH(CH3)-NH)- unit, -(Si(CH3)2-NH)- unit, -(SiR 1 It is a polymer containing (CH3)-NR3)- units. 1 (CH3)-NR 3The functional group R1 in the )-unit is H or CH3, and the functional group R3 directly bonded to N is an organic functional group that promotes the reaction. By including organic polysilazane (A) in the coating liquid 14, the reaction after the coating liquid 14 is coated on the surface 13 of the lightweight substrate 12 is promoted, and the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) can be formed on the surface 13 of the lightweight substrate 12 at an early stage. [ka] Another example of the organic polysilazane is the organic polysilazane (B), which is a -(SiH(CH3)-NH)- unit, -(SiR 1 (CH3)-NH)- units, and -(SiR 1 Functional group R of the (CH3)-NH)- unit 1 is an organic functional group that realizes high heat resistance. By including organic polysilazane (B) in the coating liquid 14, the heat resistance of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) that covers the surface 13 of the lightweight substrate 12 can be improved.

[0040] [ka] The organic polysilazane contained in the coating liquid 14 may be a mixture of multiple types of organic polysilazanes having different polymer structures. For example, the organic polysilazane may be a mixture of organic polysilazane (A) and organic polysilazane (B). According to a mixing experiment of the organic polysilazane (A) and the organic polysilazane (B), a mixture of 50 mass% of the organic polysilazane (A) and 50 mass% of the organic polysilazane (B) exhibits rust prevention properties equal to or greater than that of the organic polysilazane (A) alone, and has a shorter curing time (time to form the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b)) than that of the organic polysilazane (B) alone.

[0041] The organic polysilazane contained in the coating liquid 14 can be one selected from polymethylhydrosilazane, poly-N-methylsilazane, poly-N-(triethylsilyl)allylsilazane, poly-N-(dimethylamino)cyclohexylsilazane, and phenylpolysilazane, or a mixture of two or more of these.

[0042] The siloxane contained in the coating liquid 14 may be any one of a chain siloxane having a chain skeleton and a cyclic siloxane having a cyclic skeleton, or a mixture of two or more of them. Examples of the cyclic siloxane include hexamethylcyclotrisiloxane (CH 18 O3Si4), Octamethylcyclotetrasiloxane (C6H 24 O4Si4), decamethylcyclopentasiloxane (C 10 H 30 O5Si5), or a mixture of two or more of them can be used. The number average molecular weight of the organic polysilazane and siloxane is in the range of 3000 to 150000 g / mol.

[0043] The alkyl silicate condensate is one selected from tetramethyl orthosilicate, tetraethyl orthosilicate, tetra-n-propyl orthosilicate, tetra-i-propyl orthosilicate, tetra-n-butyl orthosilicate, tetra-sec-butyl orthosilicate, methyl polysilicate, and ethyl polysilicate, or a condensate (mixture) of two or more of them. The inert organic solvent is inert to the organic polysilazane and siloxane, and the alkyl silicate condensate, and is selected from dibutyl ether, turpentine oil, benzene, toluene, xylene, and propylene glycol monomethyl ether acetate.

[0044] Since the number average molecular weight of the organic polysilazane and the number average molecular weight of the polysiloxane are within the above ranges, the coating liquid 14 containing the organic polysilazane and / or polysiloxane can maintain a predetermined viscosity, and a glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) can be formed from the coating liquid 14. Since the coating liquid 14 is coated on the surface 13 of the lightweight substrate 12 (article) to be coated while maintaining a predetermined viscosity, even if the coating liquid 14 is coated on the surface 13 of the lightweight substrate 12 on which minute holes or meshes are formed, the coating liquid 14 does not penetrate into the lightweight substrate 12, and a glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) with a substantially uniform thickness can be formed on the surface 13 of the lightweight substrate 12.

[0045] In the coating liquid 14, the blending ratio of the organosilicon material (organic polysilazane and / or siloxane) is in the range of 30 to 60 mass% relative to the total mass of the coating liquid 14, the blending ratio of the alkyl silicate condensate is in the range of 10 to 15 mass% relative to the total mass of the coating liquid 14, and the blending ratio of the inert organic solvent is in the range of 30 to 60 mass% relative to the total mass of the coating liquid 14. If the blending ratio of the organosilicon material (organic polysilazane, siloxane) is less than 30 mass%, the content of the organosilicon material is low, and it is not possible to form a glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) of a predetermined thickness having excellent flexibility, impact resistance, and corrosion resistance on the surface 13 of the lightweight substrate 12.

[0046] If the blending ratio of the organosilicon material (organic polysilazane, siloxane) exceeds 60 mass%, the viscosity of the coating liquid 14 increases, and the thickness of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) becomes larger than necessary. Since the blending ratio of the organosilicon material (organic polysilazane, siloxane) to the total mass of the coating liquid 14 is within the above range, it is possible to create a glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) with an appropriate thickness and excellent flexibility, impact resistance, and corrosion resistance.

[0047] If the blending ratio of the alkyl silicate condensate is less than 10% by mass, the alkyl silicate condensate has a weak effect as a crosslinking agent, and a sufficient crosslinked structure is not formed in the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b). If the blending ratio of the alkyl silicate condensate exceeds 15% by mass, an unnecessary crosslinked structure is formed in the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b), and the flexibility of the glass-based coating film 10 becomes greater than necessary. Since the blending ratio of the alkyl silicate condensate to the total mass of the coating liquid 14 is within the above range, the coating liquid 14 can be used to create a glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) having an appropriate crosslinked structure and appropriate flexibility.

[0048] If the blending ratio of the inert organic solvent is less than 30% by mass, the viscosity of the coating liquid 14 becomes high, and the thickness of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) made from it becomes larger than necessary. If the blending ratio of the inert organic solvent exceeds 60% by mass, the viscosity of the coating liquid 14 becomes lower than necessary, and it is not possible to form a glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) of a predetermined thickness having excellent flexibility, impact resistance, and corrosion resistance on the surface 13 of the lightweight substrate 12. Since the blending ratio of the inert organic solvent to the total mass of the coating liquid 14 is within the above range, it is possible to use the coating liquid 14 to make a glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) of appropriate viscosity having excellent flexibility, impact resistance, and corrosion resistance.

[0049] The coating liquid 14 contains an organosilicon material (organic polysilazane and / or siloxane) in the range of 30-60 mass% and an alkyl silicate condensate in the range of 10-15 mass% relative to its total mass, so that the formation rate of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) made from the coating liquid 14 can be appropriately controlled. Specifically, the hydrolysis of the alkyl silicate condensate proceeds faster than the condensation of the organic polysilazane and / or siloxane, so that the progress of the condensation reaction of the organic polysilazane and / or siloxane can be delayed by first consuming a portion of water (H2O) in the hydrolysis of the alkyl silicate condensate, and the formation rate of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) can be controlled. Furthermore, since the hydrolysis of the alkyl silicate condensate occurs first, a crosslinked structure can be reliably formed in the glass-based coating film 10 (the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b) to impart flexibility.

[0050] In addition, since the organic solvent is selected from dibutyl ether, turpentine oil, benzene, toluene, xylene, and propylene glycol monomethyl ether acetate, which are inactive against organic polysilazane, siloxane, and alkyl silicate condensates, the condensation reaction of organic polysilazane and / or siloxane does not progress rapidly, and the formation rate of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) can be appropriately controlled. The coating liquid 14 that can control the formation rate of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) can easily perform the coating work on the surface 13 of the lightweight substrate 12.

[0051] Low molecular weight silanes are made from chlorosilanes, and contain multiple organic functional groups and hydrolyzable alkoxy groups in one molecule, forming an amorphous glass coating through dehydration crosslinking. Low molecular weight silanes have multifunctional groups that strongly bond with organic substances, and hydrolyzable alkoxy groups that strongly bond with inorganic substances. Low molecular weight silanes can be made into low molecular weight liquids by 100% functionalization (high concentration of vitrification components and solvent-free possible). Furthermore, they do not contain volatile silanol groups, so they have high storage and stability. The hardening speed of low molecular weight silanes can be adjusted, and they can be hand-painted. Low molecular weight silanes can be hand-painted even without solvent (highest concentration of vitrification components) because they are low molecular weight. Furthermore, because they are low molecular weight, they have high wettability and leveling properties, and the glossy aesthetic quality of the finished product is stable.

[0052] The multiple filler particles 15 mixed into the coating liquid 14 are one type selected from among particulate Si (silicon), particulate SiO2 (silicon dioxide), particulate Al2O3 (aluminum oxide), particulate ZrO2 (zirconia oxide), particulate AlN (aluminum nitride), particulate Si3N4 (silicon nitride), and particulate SiC (single crystal silicon carbide), or composite filler particles comprising a mixture of two or more types of such filler particles 15 are used.

[0053] The Young's modulus (GPa) of the filler particles 15 is calculated by multiplying the density (g / cm 3 The Young's modulus (GPa) of the filler particles 15 divided by its density (g / cm 3 ) is 30 or more, it is possible to reliably increase the Young's modulus (GPa) of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) made from the coating liquid 14 containing the filler particles 15, and it is possible to reliably increase the Young's modulus (GPa) of the composite material 11 (club head 17 and shaft 18 of a golf club 16, rod 20 of a fishing rod 19, propeller 21, rotor 22) on which the glass-based coating film 10 is formed.

[0054] The filler particles 15 have a plate-like shape. The filler particles 15 may have an irregular shape. The filler particles 15 have an average particle size D 50 The average particle diameter D of the filler particles 15 is in the range of 0.1 μm or more and 20 μm or less. 50 If the average particle size D of the filler particles 15 is less than 0.1 μm, the Young's modulus (GPa) of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) made from the coating liquid 14 containing the filler particles 15 cannot be increased, and the Young's modulus (GPa) of the composite material 11 (club head 17 and shaft 18 of the golf club 16, rod 20 of the fishing rod 19, propeller 21, rotor 22) on which the glass-based coating film 10 is formed cannot be increased. 50 If the thickness exceeds 20 μm, the adhesion of the glass-based coating film 10 (inorganic glass coating film 10 a or organic / inorganic hybrid glass coating film 10 b) to the surface 13 of the lightweight substrate 12 decreases significantly, making it impossible to form a smooth glass-based coating film 10 on the surface 13 of the lightweight substrate 12.

[0055] The coating liquid 14 contains filler particles 15 having an average particle size D50 is within the above range, the Young's modulus (GPa) of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) made from the coating liquid 14 can be increased, and the Young's modulus (GPa) of the composite material 11 (club head 17 and shaft 18 of a golf club 16, rod 20 of a fishing rod 19, propeller 21, rotor 22) on which the glass-based coating film 10 is formed can be increased, and the glass-based coating film 10 has excellent adhesion to the surface 13 of the lightweight substrate 12 and can be formed smoothly on the surface 13 of the lightweight substrate 12.

[0056] The content of the filler particles 15 mixed in the coating liquid 14 is in the range of 5 to 50 volumes. If the content of the filler particles 15 mixed in the coating liquid 14 is less than 5 volumes, the content of the filler particles 15 in the coating liquid 14 is small, and the Young's modulus (GPa) of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) made from the coating liquid 14 mixed with the filler particles 15 cannot be increased, and the Young's modulus (GPa) of the composite material 11 (club head 17 and shaft 18 of a golf club 16, rod 20 of a fishing rod 19, propeller 21, rotor 22) on which the glass-based coating film 10 is formed cannot be increased. If the content of filler particles 15 mixed in the coating liquid 14 exceeds 50 by volume, the adhesion of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) to the surface 13 of the lightweight substrate 12 is significantly reduced, and a smooth glass-based coating film 10 cannot be formed on the surface 13 of the lightweight substrate 12.

[0057] Since the coating liquid 14 has a content of filler particles 15 mixed therein within the above range, it is possible to increase the Young's modulus (GPa) of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) produced from the coating liquid 14, and to increase the Young's modulus (GPa) of the composite material 11 (club head 17 and shaft 18 of a golf club 16, rod 20 of a fishing rod 19, propeller 21, rotor 22) on which the glass-based coating film 10 is formed. In addition, the coating liquid 14 has excellent adhesion to the surface 13 of the lightweight substrate 12, and a smooth glass-based coating film 10 can be formed on the surface 13 of the lightweight substrate 12.

[0058] The lightweight substrate 12 to be coated with the coating liquid 14 (the lightweight substrate 12 on which the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b is formed) is one selected from CFRP (carbon fiber composite material), which is a composite material in which carbon fiber is solidified with resin (mainly epoxy resin), FRP (fiber reinforced plastic) in which fibers such as glass fiber and carbon fiber are mixed with epoxy resin or phenolic resin, ABS resin, which is a thermoplastic resin formed from three types of monomers, acrylonitrile (A), butadiene (B), and styrene (S), polycarbonate, which is a thermoplastic resin in which all the bonding parts between monomer units are composed of carbonate groups, carbon fiber polycarbonate (carbon fiber reinforced polycarbonate) in which carbon fiber is mixed into polycarbonate, aluminum alloy (Al alloy), which is an alloy mainly composed of aluminum, and magnesium alloy (Mg alloy), which is an alloy mainly composed of magnesium. There is no particular restriction on the shape of the molded product made from these lightweight substrates. The lightweight substrate 12 has a density of 3.0 g / cm 3 The lightweight substrate 12 (article) to be coated with the coating liquid 14 includes a club head 17 and a shaft 18 of a golf club 16, a rod 20 of a fishing rod 19, a propeller 21, and a rotor 22.

[0059] The coating liquid 14 is coated or sprayed onto the surface 13 of the lightweight substrate 12 (article) to be coated, and chemically reacts with moisture to form (deposit) a single-layer or multi-layer ultra-thin glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b). The inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b is deposited as a coating having an average thickness in the range of 0.5 μm to 20 μm.

[0060] The average thickness of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) is in the range of 0.5 μm to 20 μm. If the average thickness of the glass-based coating film 10 is less than 0.5 μm, the Young's modulus (GPa) of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) cannot be increased, and the Young's modulus (GPa) of the composite material 11 on which the glass-based coating film 10 is formed (club head 17 and shaft 18 of golf club 16, rod 20 of fishing rod 19, propeller 21, rotor 22) cannot be increased, and the strength of the glass-based coating film 10 is reduced, losing its protective function, and the surface 13 of the lightweight substrate 12 cannot be sufficiently protected. Since the average film thickness of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) is within the above range, the Young's modulus (GPa) of the glass-based coating film 10 made from the coating liquid 14 can be increased, and the Young's modulus (GPa) of the composite material 11 (club head 17 and shaft 18 of a golf club 16, rod 20 of a fishing rod 19, propeller 21, rotor 22) on which the glass-based coating film 10 is formed can be increased.

[0061] There is no particular limitation on the method of coating the surface 13 (contact surface) of the lightweight substrate 12 with the coating liquid 14, and the coating is performed by a coating method suited to the shape of the lightweight substrate 12 to be coated (covered). For example, coating can be performed by spraying, dipping, brushing, roll coating, gravure coating, flexography, inkjet, etc. There is no particular limitation on the amount of coating (application amount) of the coating liquid 14, and the amount of coating is determined according to the surface performance required for the lightweight substrate 12 to be coated. Generally, it is 0.1 to 20 g / m in terms of solid content. 2 The coating amount is 0.1g / m 2 If the coating amount is less than 20 g / m, the glass-based coating film 10 (the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b) having the desired properties will not be formed. 2 If it exceeds this value, the thickness of the glass coating film 10 (the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b) will increase more than necessary, and the flexibility of the glass coating film 10 will be lost.

[0062] In addition, as a pretreatment process prior to the coating process of the coating liquid 14, water (H2O) such as purified water may be sprayed onto the surface 13 of the lightweight substrate 12 to adhere the water to the surface 13 of the lightweight substrate 12. In this way, a chemical reaction between the water adhered to the surface 13 of the lightweight substrate 12 and the components contained in the coating liquid 14 is promoted, and a glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) can be rapidly formed on the surface 13 of the lightweight substrate 12, and a strong glass-based coating film 10 can be formed on the surface 13 of the lightweight substrate 12.

[0063] Furthermore, as a pretreatment step prior to the coating step of the coating liquid 14, a coating liquid mainly composed of inorganic polysilazane can be coated as a primer on the surface 13 of the lightweight substrate 12. For example, when a solution of inorganic polysilazane (1 wt % solution) is coated and then the coating liquid 14 is coated, the rust prevention (durability) of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) is improved compared to when only the coating liquid 14 is simply coated.

[0064] The mechanism by which the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) is formed on the surface 13 of the lightweight substrate 12 is as follows. In the formation (film formation) of the inorganic glass coating film 10a, the surface 13 of the lightweight substrate 12 is coated with the coating liquid 14 by a coating process, and then the surface 13 of the lightweight substrate 12 is irradiated with ultraviolet rays while irradiating with infrared rays to heat the surface 13 of the lightweight substrate 12 to 400°C or higher. In the formation (film formation) of the organic / inorganic hybrid glass coating film 10b, the surface 13 of the lightweight substrate 12 is coated with the coating liquid 14 by a coating process, and then the surface 13 of the lightweight substrate 12 is left at room temperature (normal temperature) without heating. Alternatively, the surface 13 of the lightweight substrate 12 is coated with the coating liquid 14, and then the surface 13 of the lightweight substrate 12 is irradiated with ultraviolet rays while being left at room temperature (normal temperature). Alternatively, after coating the surface 13 of the lightweight substrate 12 with the coating liquid 14, the surface 13 of the lightweight substrate 12 is irradiated with ultraviolet light while irradiating with infrared light to heat the surface 14 of the lightweight substrate 12 to a temperature of less than 400°C.

[0065] As shown in FIG. 2(a), a small amount of moisture (water droplets) is attached to the surface 13 of the lightweight substrate 12 due to condensation or humidity in the air (including the case where water (H2O) is sprayed). When the surface 13 of the lightweight substrate 12 is coated with a thin film of the coating liquid 14 by a coating process, the -(SiR 1 R 2 -NR3 )-unit components and / or -(SiR 1 R 2 -NR 3 The )-unit component chemically reacts with moisture (H20) in the air, and an inorganic glass coating film 10a or an organic / inorganic hybrid glass coating film 10b (glass coating layer (amorphous glass coating)) having an organic composite structure (-(Si(CH3)2-O-Si(CH3)2)-unit in an example of the structural image of the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b shown in Figures 3 and 4) in which an organic functional group is bonded as a side chain to a part of the main chain by a siloxane bond (Si-O-Si) is generated on the surface 13 of the lightweight substrate 12. Note that the inorganic glass coating film 10a is vitrified (inorganized) at approximately 100%. Also, a small amount of gas (NH3, H2) is generated as a by-product of the above chemical reaction. These gases do not remain on the surface of the article but are volatilized (emitted) into the atmosphere.

[0066] As shown in FIG. 2(b), the coating liquid 14 containing organic polysilazane and / or siloxane undergoes a chemical reaction (deammonia cross-linking) with moisture contained in the air in the surface layer 23 in contact with the air, whereby gases such as hydrogen and ammonia, which are by-products of the glass-based coating film 10 (the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b), volatilize from the surface 13 to the outside air, and a coating layer 24 is formed (generated) on the surface side of the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b.

[0067] The coating liquid 14 coated on the surface 13 of the lightweight substrate 12 undergoes a chemical reaction (deammonia cross-linking) with moisture (water droplets) attached to the surface 13 or with hydroxyl groups -OH (see Figures 3 and 4) present as terminal ends on the surface 13 in the back layer 25 in contact with the surface 13 of the lightweight substrate 12, causing gases such as hydrogen and ammonia to rise within the coating layer 24 and volatilize from the surface 13 to the outside air, and forming (generating) a coating layer 24 on the back side of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b).

[0068] First, the coating layer 24 (vitrified (inorganic) or vitrified (inorganic) and organicized parts) is generated in the surface layer 23 and the back layer 25 of the coating liquid 14. Next, the coating layer 24 (vitrified (inorganic) and organicized parts) is formed and expanded from the surface layer 23 side toward the back layer 25 side, and the coating layer 24 (vitrified (inorganic) or vitrified (inorganic) and organicized parts) is expanded from the back layer 25 side toward the surface layer 23 side, so that the coating layer 24 (vitrified (inorganic) or vitrified (inorganic) and organicized parts) of the intermediate layer 26 is successively formed (generated), and finally, the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) is formed (generated) on the surface layer 23 in contact with the outside air, the back layer 25 in contact with the surface 13 of the lightweight substrate 12, and the intermediate layer 26 between the surface layer 23 and the back layer 25.

[0069] The inorganic glass coating film 10a made of organic polysilazane and / or siloxane is a glass coating layer that is approximately 100%. The inorganic glass coating film 10a is mainly composed of SiO2 produced by reacting organic polysilazane and / or siloxane, and thus a glass coating layer that spreads easily in a plane and has high density and high hardness (pencil hardness of about 6H to 9H) is formed. The inorganic glass coating film 10a is formed into a thin film by the coating liquid 14 containing organic polysilazane and / or siloxane.

[0070] The average thickness of the inorganic glass coating film 10a is in the range of 0.5 μm to 20 μm. If the average thickness of the inorganic glass coating film 10a is less than 0.5 μm, the Young's modulus (GPa) of the inorganic glass coating film 10a made from the coating liquid 14 containing the filler particles 15 cannot be increased, and the Young's modulus (GPa) of the composite material 11 (club head 17 and shaft 18 of the golf club 16, rod 20 of the fishing rod 19, propeller 21, rotor 22) on which the inorganic glass coating film 10a is formed cannot be increased, and the strength of the inorganic glass coating film 10a decreases, losing its protective function, and the surface 13 of the lightweight substrate 12 cannot be sufficiently protected. If the average thickness of the inorganic glass coating film 10a exceeds 20 μm, the flexibility of the inorganic glass coating film 10a decreases, and the inorganic glass coating film 10a may peel off from the surface 13 due to deformation of the surface 13 of the lightweight substrate 12. Although the inorganic glass coating film 10a is a coating film whose main component is SiO2, it has excellent flexibility, and coupled with the anchoring effect of the anchor portion 27, it will not peel off even if the surface 13 of the lightweight substrate 12 is deformed by a cloth material or the like, and can maintain the coating state of the inorganic glass coating film 10a by following the deformation of the surface 13, and can reliably protect the surface 13 of the lightweight substrate, preventing damage to the surface 13.

[0071] The organic / inorganic hybrid glass coating film 10b made of organic polysilazane and / or siloxane is composed of a glass coating layer (amorphous glass coating layer) and an organic coating layer. The organic / inorganic hybrid glass coating film 10b is mainly composed of SiO2 generated by reacting organic polysilazane and / or siloxane, and thus a coating layer that spreads easily in a plane and has high density and high hardness (pencil hardness of about 6H to 9H) is formed. The low molecular weight silane contained in the coating liquid 14 forms an organic / inorganic hybrid glass coating film 10b (amorphous glass coating) by dehydration crosslinking. The organic / inorganic hybrid glass coating film 10b made from the low molecular weight silane is formed of a glass coating layer (amorphous glass coating layer) and an organic coating layer. The organic / inorganic hybrid glass coating film 10b is formed into a thin film because the coating liquid 14 contains organic polysilazane and / or siloxane or low molecular weight silane.

[0072] The average thickness of the organic / inorganic hybrid glass coating film 10b is in the range of 0.5 μm to 20 μm. If the average thickness of the organic / inorganic hybrid glass coating film 10b is less than 0.5 μm, the Young's modulus (GPa) of the organic / inorganic hybrid glass coating film 10b made from the coating liquid 14 containing the filler particles 15 cannot be increased, and the Young's modulus (GPa) of the composite material 11 (club head 17 and shaft 18 of the golf club 16, rod 20 of the fishing rod 19, propeller 21, rotor 22) on which the organic / inorganic hybrid glass coating film 10b is formed cannot be increased. In addition, the strength of the organic / inorganic hybrid glass coating film 10b is reduced, losing its protective function, and the surface 13 of the lightweight substrate 12 (article) cannot be sufficiently protected. If the average thickness of the organic / inorganic hybrid glass coating film 10b exceeds 20 μm, the flexibility of the organic / inorganic hybrid glass coating film 10b decreases, and the organic / inorganic hybrid glass coating film 10b may peel off from the surface 13 due to deformation of the surface 13 of the lightweight substrate 12. Although the organic / inorganic hybrid glass coating film 10b is a coating film mainly composed of SiO2, it has excellent flexibility, and coupled with the anchor effect of the anchor portion 27, it will not peel off even if the surface 13 of the lightweight substrate 12 is a material that causes deformation such as a cloth material, and can maintain the coating state of the organic / inorganic hybrid glass coating film 10b by following the deformation of the surface 13, and can reliably protect the surface 13 of the lightweight substrate, thereby preventing damage to the surface 13.

[0073] As shown in the structural image of the inorganic glass coating film 10a in Fig. 3 or the structural image of the organic / inorganic hybrid glass coating film 10b in Fig. 4, a crosslinking reaction occurs between a hydrolysis product having a -(Si(OH)2-O-Si(OH)2)- unit generated by chemically reacting an alkyl silicate condensate with water and a part of the main chain of the siloxane bond (Si-O-Si) in each coating layer (surface layer 23, intermediate layer 26, back layer 25), and a crosslinked structure is formed, so that the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b has a dense and flexible structure. In addition, it is assumed that the formation of the crosslinked structure allows the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b to have a hydrophobic methyl group (CH3) derived from organic polysilazane and / or siloxane and a hydrophilic hydroxyl group (OH) derived from the hydrolysis product of the alkyl silicate condensate to be coordinated on the surface of the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b.

[0074] As shown in FIG. 2(c), the surface 13 of the lightweight substrate 12 before being coated with the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b has many micro-level fine unevenness formed by small scratches generated during the manufacturing process, etc., unless a special surface treatment such as mirror finishing is performed. The coating liquid 14 is coated on the surface 13 of the lightweight substrate 12 and hardens while penetrating into the unevenness, so that the anchor portion 27 of the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b that has hardened and penetrated into the unevenness exerts an anchor effect, and the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b adheres more firmly to the surface 13 of the lightweight substrate 12. The organic / inorganic hybrid glass coating film 10b made from low molecular weight silane is a low molecular weight, so it penetrates (permeates) into the entire interior of the unevenness of the surface 13 of the lightweight substrate 12 and hardens throughout the entire interior of the unevenness, exerting a strong anchor effect.

[0075] When the surface 13 of the lightweight substrate 12 is a smooth surface with almost no unevenness, the surface 13 may be roughened to form unevenness with an average roughness of about 1 to 500 μm on the surface 13 as a pretreatment for coating the coating liquid 14. By performing the roughening treatment in this manner, an anchor effect can be obtained by the anchor portion 27 of the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b. After the roughening treatment, a cleaning treatment is performed to blow away metal powder, plastic powder, etc. generated on the surface 13 of the lightweight substrate 12 using an air injection means such as an air gun. After the cleaning treatment, condensation, etc. is generated on the surface 13 of the lightweight substrate 12 by leaving it for a predetermined time, and naturally occurring moisture is attached to the surface 13.

[0076] In this case, after the surface 13 of the lightweight substrate 12 is roughened and cleaned, moisture is actively applied to the surface 13 on which unevenness has been formed by the roughening using a moisture application means such as a sprayer, and then the coating liquid 14 is coated. In this manner, it is possible to promote a chemical reaction between the moisture applied to the surface 13 of the lightweight substrate 12 and the coating liquid 14 in contact with the surface 13. Note that moisture may be applied by a moisture application means without applying a roughening treatment to the surface 13 of the lightweight substrate 12.

[0077] The unevenness initially formed on the surface 13 of the lightweight substrate 12 before being coated with the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b made from organic polysilazane and / or siloxane is covered by the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b, so that the surface 13 becomes smoother after coating than before coating.

[0078] The glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) formed on the surface 13 of the lightweight substrate 12 has filler particles 15 (at least one of Si, SiO2, Al2O3, ZrO2, AlN, Si3N4, and SiC) mixed into the coating liquid 14 that forms the films 10a and 10b, so that a plurality of filler particles 15 are dispersed and mixed inside the films 10a and 10b formed by hardening the coating liquid 14.

[0079] The content of the filler particles 15 dispersed and mixed inside the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) is in the range of 5 to 50 volumes. If the content of the filler particles 15 dispersed and mixed inside the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) is less than 5 volumes, the content of the filler particles 145 in the glass-based coating film 10 is small, and the Young's modulus (GPa) of the glass-based coating film 10 cannot be increased, and the Young's modulus (GPa) of the composite material 11 on which the glass-based coating film 10 is formed (club head 17 and shaft 18 of a golf club, rod 20 of a fishing rod 19, propeller 21, rotor 22) cannot be increased. When the content of filler particles 15 dispersed and mixed inside the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) exceeds 50 by volume, the adhesion of the glass-based coating film 10 to the surface 13 of the lightweight substrate 12 is significantly reduced, and a smooth glass-based coating film 10 cannot be formed on the surface 13 of the lightweight substrate 12.

[0080] Since the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) has a content of filler particles 15 dispersed therein within the above range, the Young's modulus (GPa) of the glass-based coating film 10 can be increased, and the Young's modulus (GPa) of the composite material 11 (club head 17 and shaft 18 of a golf club, rod 20 of a fishing rod 19, propeller 21, rotor 22) on which the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) is formed can be increased. In addition, the glass-based coating film 10 has excellent adhesion to the surface 13 of the lightweight substrate 12, and a smooth glass-based coating film 10 can be formed on the surface 13 of the lightweight substrate 12.

[0081] The composite member 11 is formed by forming a glass-based coating film 10 having a plurality of plate-shaped filler particles 15 dispersed therein on an elastically deformable lightweight substrate 12, and the density of the lightweight substrate 12 is 3.0 g / cm 3 The Young's modulus (GPa) of the filler particles 15 is less than or equal to the density (g / cm 3 ) is 30 or more, the filler particles 15 (at least one type of Si, SiO2, Al2O3, ZrO2, AlN, Si3N4, and SiC) can improve the Young's modulus of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b), and the Young's modulus of the lightweight substrate 12 (CFRP, FRP, ABS resin, polycarbonate, carbon fiber polycarbonate, aluminum alloy (Al alloy), magnesium alloy (Mg alloy)) on which the glass-based coating film 10 is formed can be improved.

[0082] In the composite member 11, a glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) in which filler particles 15 of at least one type selected from the group consisting of Si, SiO2, Al2O3, ZrO2, AlN, Si3N4, and SiC are dispersed and mixed is formed on the surface 13 of the lightweight substrate 12. This improves the Young's modulus (hardness) of the lightweight substrate 12, and even if a large air resistance acts on the lightweight substrate 12 (CFRP, FRP, ABS resin, polycarbonate, carbon fiber polycarbonate, aluminum alloy (Al alloy), magnesium alloy (Mg alloy)) that forms the composite member 11 when the composite member 11 moves or rotates at high speed, the generation of vibration in the composite member 11 when the composite member 11 moves or rotates at high speed can be suppressed, thereby improving the propulsive force of the composite member 11 and reducing the noise generated when the composite member 11 moves or rotates at high speed.

[0083] Fig. 5 is a perspective view of a golf club 16 shown as an example, and Fig. 6 is a cross-sectional view taken along line AA in Fig. 5. Fig. 7 is a cross-sectional view taken along line BB in Fig. 5. The golf club 16 shown in Fig. 5 is a driver, and is formed of a club head 17, a shaft 18 having one end connected to the club head 17, and a grip made of a resin material or the like and fitted to the other end of the shaft 18. The golf club 16 includes fairway woods, utilities, irons (long irons, middle irons, short irons), and wedges.

[0084] The above-mentioned glass-based coating film 10 (inorganic coating film 10a or organic / inorganic hybrid coating film 10b) is formed (covered) on the entire surface 13 (entire face area) of a club head 17 of a golf club 16 shown in Fig. 5 and the entire peripheral surface 13 (entire outer peripheral surface area) of a shaft 18 (composite member 11). The glass-based coating film 10 may not be formed on the entire surface 13 of the club head 17 of the golf club 16, and may be formed only on the entire peripheral surface 13 of the shaft 18. In addition, when the shaft 18 is a hollow shaft, the glass-based coating film 10 may be formed on the inner peripheral surface (entire inner peripheral surface area) of the hollow shaft that encases the hollow.

[0085] The club head 17 is made of a titanium alloy. There is no particular limit to the material of the club head 17, and in addition to titanium alloy, the club head 17 may be made of various materials such as soft iron, stainless steel, full titanium, aluminum alloy, and carbon. The shaft 18 is made of carbon fiber polycarbonate (lightweight base material 12). There is no particular limit to the material of the shaft 18, and the shaft may be made of steel. The shaft 18 may also be a solid shaft or a hollow shaft. The shaft 18 of the golf club 16 elastically deforms during the swing.

[0086] The glass-based coating film 10 (inorganic coating film 10a or organic / inorganic hybrid coating film 10b) formed on the entire surface 13 of the club head 17 of the golf club 16 and the entire peripheral surface 13 of the shaft 18 is made from the above-mentioned coating liquid 14 consisting of a liquid organosilicon material (silicon material) made of at least one of organic polysilazane (polysilazane) and siloxane, an alkyl silicate condensate, and an inert organic solvent, and having a plurality of plate-shaped filler particles 15 (at least one of Si, SiO2, Al2O3, ZrO2, AlN, Si3N4, and SiC) mixed therein, or is made from the above-mentioned coating liquid 14 consisting of a low molecular weight silane mixed with a plurality of plate-shaped filler particles 15 (at least one of Si, SiO2, Al2O3, ZrO2, AlN, Si3N4, and SiC).

[0087] To form (deposit) an inorganic glass coating film 10a, which is a glass-based coating film 10, on the entire surface 13 of the club head 17 and the entire peripheral surface 13 of the shaft 18, a coating liquid 14 containing filler particles 15 is applied to the club head 17 and the shaft 18, and then the surface 13 of the club head 17 and the peripheral surface 13 of the shaft 18 are irradiated with ultraviolet light while irradiating with infrared light to heat the surface 13 of the club head 17 and the peripheral surface 13 of the shaft 18 to 400° C. or higher. An inorganic glass coating film 10a having an average thickness in the range of 0.5 μm to 20 μm is formed (deposited) on the surface 13 of the club head 17 and the peripheral surface 13 of the shaft 18. The club head 17 and shaft 18 of the golf club 16 on which the thin inorganic glass coating film 10a mainly composed of SiO2 as described above is formed (deposited) have an increased Young's modulus and are provided with high flexibility, impact resistance, water repellency, and stain and rust resistance. In addition, the inorganic glass coating film has high film-forming properties and adhesion that make it difficult for it to peel off even when the club head 17 and shaft 18 are twisted or bent.

[0088] To form (form) the organic / inorganic hybrid glass coating film 10b, which is the glass-based coating film 10, on the entire surface 13 of the club head 17 and the entire peripheral surface 13 of the shaft 18, the coating liquid 14 containing the filler particles 15 is applied to the club head 17 and the shaft 18, and then the surface 13 of the club head 17 and the peripheral surface 13 of the shaft 18 are left at room temperature (normal temperature) without being heated. Alternatively, after the coating liquid 14 is applied to the club head 17 and the shaft 18, the surface 13 of the club head 17 and the peripheral surface 13 of the shaft 18 are irradiated with ultraviolet light while being left at room temperature (normal temperature). Alternatively, after the coating liquid 14 is applied to the club head 17 and the shaft 18, the surface 13 of the club head 17 and the peripheral surface 13 of the shaft 18 are irradiated with ultraviolet light while being irradiated with infrared light to heat the surface 13 of the club head 17 and the peripheral surface 13 of the shaft 18 to a temperature of less than 400°C. An organic / inorganic hybrid glass coating film having an average thickness in the range of 0.5 μm to 20 μm is formed (deposited) on the surface 13 of the club head 17 and the circumferential surface 13 of the shaft 18. The club head 17 and shaft 18 of the golf club 16 on which the thin organic / inorganic hybrid glass coating film 10b mainly composed of SiO2 is formed (deposited) have an increased Young's modulus, and are provided with high flexibility, impact resistance, water repellency, and stain and rust resistance, as well as high film formability and adhesion such that the organic / inorganic hybrid glass coating film 10b is not easily peeled off even when the club head 17 and shaft 18 are twisted or bent.

[0089] If the average thickness of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) formed on the entire surface 13 of the club head 17 and the entire peripheral surface 13 of the shaft 18 is less than 0.5 μm, the Young's modulus (GPa) of the glass-based coating film 10 cannot be increased, and the Young's modulus (GPa) of the club head 17 and the shaft 18 on which the glass-based coating film 10 is formed cannot be increased. In addition, the strength of the glass-based coating film 10 decreases and its protective function is lost, so that the surface 13 of the club head 17 and the peripheral surface 13 of the shaft 18 cannot be sufficiently protected. If the average thickness of the glass-based coating film 10 formed on the entire surface 13 of the club head 17 and the entire peripheral surface 13 of the shaft 18 exceeds 20 μm, the flexibility of the glass-based coating film 10 decreases, and the glass-based coating film 10 may peel off from the surface 13 of the club head 17 and the peripheral surface 13 of the shaft 18 due to deformation (elastic deformation) of the club head 17 and the shaft 18.

[0090] Since the average thickness of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) in which the filler particles 15 are dispersed and mixed is within the above range, the Young's modulus (GPa) of the glass-based coating film 10 can be increased, and the Young's modulus (GPa) of the club head 17 and shaft 18 on which the glass-based coating film 10 is formed can be increased. Even if the club head 17 or shaft 18 of the golf club 16 is deformed (elastically deformed), the glass-based coating film 10 does not peel off from the surface 13 of the club head 17 and the circumferential surface 13 of the shaft 18, and the coating state of the glass-based coating film 10 can be maintained by following the deformation of the club head 17 and the shaft 18, and the surface 13 of the club head 17 and the circumferential surface 13 of the shaft 18 can be reliably protected, and the surface 13 of the club head 17 and the circumferential surface 13 of the shaft 18 can be prevented from being scratched.

[0091] The filler particles 13 dispersed and mixed in the glass-based coating film 10 (the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b) formed on the entire surface 13 of the club head 17 and the entire peripheral surface 13 of the shaft 18 have a Young's modulus (GPa) and a density (g / cm 3 ) is 30 or more. In the golf club 16, the Young's modulus (GPa) of the filler particles 15 is divided by its density (g / cm 3 ) is 30 or more, the Young's modulus (GPa) of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) made from the coating liquid 14 containing the filler particles 15 can be reliably increased, and the Young's modulus (GPa) of the club head 17 and shaft 18 on which the glass-based coating film 10 is formed can be reliably increased.

[0092] The filler particles 15 dispersed and mixed in the glass-based coating film 10 (the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b) formed on the entire surface 13 of the club head 17 and the entire peripheral surface 13 of the shaft 18 have an average particle diameter D 50 The average particle diameter D of the filler particles 15 is in the range of 0.1 μm or more and 20 μm or less. 50 If the average particle size D of the filler particles 15 is less than 0.1 μm, the Young's modulus (GPa) of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) made from the coating liquid 14 containing the filler particles 15 cannot be increased, and the Young's modulus (GPa) of the club head 17 and shaft 18 on which the glass-based coating film 10 is formed cannot be increased. 50 If the thickness exceeds 20 μm, the adhesion of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) to the surface 13 of the club head 17 and the peripheral surface 13 of the shaft 18 will be significantly reduced, making it impossible to form a smooth glass-based coating film 10 on the surface 13 of the club head 17 and the peripheral surface 13 of the shaft 18.

[0093] The golf club 16 has a filler particle 15 having an average particle diameter D of 10 mm or less that is dispersed and mixed inside the glass-based coating film 10 (the inorganic glass coating film 10 a or the organic / inorganic hybrid glass coating film 10 b ) formed on the entire surface 13 of the club head 17 and the entire peripheral surface 13 of the shaft 18 . 50 is in the above range, the Young's modulus (GPa) of the glass-based coating film 10 can be reliably increased, and the Young's modulus (GPa) of the club head 17 and shaft 18 on which the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) is formed can be reliably increased. In addition, the glass-based coating film 10 has excellent adhesion to the surface 13 of the club head 17 and the circumferential surface 13 of the shaft 18, and a smooth glass-based coating film 10 can be formed on the surface 13 of the club head 17 and the circumferential surface 13 of the shaft 18.

[0094] The filler particles 15 dispersed and mixed inside the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) formed on the entire surface 13 of the club head 17 and the entire circumferential surface 13 of the shaft 18 have a content in the glass-based coating film 10 in the range of 5 to 50 volumes. If the content of the filler particles 15 is less than 5 volumes, the content of the filler particles 15 in the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) is low, making it impossible to increase the Young's modulus (GPa) of the glass-based coating film 10, and making it impossible to increase the Young's modulus (GPa) of the club head 17 and shaft 18 on which the glass-based coating film 10 is formed. If the content of filler particles 15 exceeds 50 by volume, the adhesion of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) to the surface 13 of the club head 17 and the peripheral surface 13 of the shaft 18 is significantly reduced, and a smooth glass-based coating film 10 cannot be formed on the surface 13 of the club head 17 and the peripheral surface 13 of the shaft 18.

[0095] In the golf club 16, the content of filler particles 15 dispersed and mixed inside the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) formed on the entire surface 13 of the club head 17 and the entire circumferential surface 13 of the shaft 18 is within the above-mentioned range, so that the Young's modulus (GPa) of the glass-based coating film 10 can be reliably increased, and the Young's modulus (GPa) of the club head 17 and shaft 18 on which the glass-based coating film 10 is formed can be reliably increased. In addition, the glass-based coating film 10 has excellent adhesion to the surface 13 of the club head 17 and the circumferential surface 13 of the shaft 18, and a smooth glass-based coating film 10 can be formed on the surface 13 of the club head 17 and the circumferential surface 13 of the shaft 18.

[0096] A golf club 16 has a glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) having a plurality of filler particles 15 dispersed and mixed therein formed over the entire surface 13 of a club head 17 and the entire peripheral surface 13 of a shaft 18 (composite member 11), whereby the filler particles 15 can improve the Young's modulus of the glass-based coating film 10, thereby improving the Young's modulus of the club head 17 and shaft 18 on which the glass-based coating film 10 is formed.

[0097] The golf club 16 has a glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) having a plurality of filler particles 15 dispersed and mixed therein formed over the entire surface 13 of the club head 17 and the entire circumferential surface 13 of the shaft 18, thereby making it possible to increase the Young's modulus of the club head 17 and the shaft 18. Therefore, even if a large air resistance acts on the shaft 18 when the golf club 16 is swung, the occurrence of vibration in the shaft 18 during the swing can be suppressed, the wobble of the club head 17 can be suppressed, the flight distance of the golf ball can be increased, and the flight direction of the ball can be stabilized.

[0098] FIG. 8 is a perspective view of a fishing rod 19 shown as an example, and FIG. 9 is a cross-sectional view taken along the line CC in FIG. 8. The fishing rod 19 shown in FIG. 8 is a telescopic reel rod, but the fishing rod 19 includes all fishing rods, such as a jointed reel rod, a telescopic rod, a jointed rod, and a one-piece rod. The types of rod 20 include all rods, such as sea bass / shore casting rods, egging rods, light saltwater lure rods, offshore rods, bass rods, trout rods, reef / breakwater rods, boat rods, casting rods, and mountain stream rods. The entire peripheral surface 13 (entire surface area) of the rod 20 of the fishing rod 19 in FIG. 8 is formed (coated) with the above-mentioned glass-based coating film 10 (inorganic coating film 10a or organic / inorganic hybrid coating film 10b). The fishing rod 19 is made of carbon or glass fiber. The fishing rod 19 elastically deforms during casting.

[0099] The glass-based coating film 10 (inorganic coating film 10a or organic / inorganic hybrid coating film 10b) formed on the entire peripheral surface 13 of the rod 20 of the fishing rod 19 is made from the above-mentioned coating liquid 14, which is made of a liquid organosilicon material (silicon material) consisting of at least one of organic polysilazane (polysilazane) and siloxane, an alkyl silicate condensate, and an inert organic solvent, and in which a plurality of plate-shaped filler particles 15 (at least one of Si, SiO2, Al2O3, ZrO2, AlN, Si3N4, and SiC) are mixed, or is made from the above-mentioned coating liquid 14, in which a plurality of plate-shaped filler particles 15 (at least one of Si, SiO2, Al2O3, ZrO2, AlN, Si3N4, and SiC) are mixed into a low molecular weight silane.

[0100] To form (deposit) an inorganic glass coating film 10a, which is a glass-based coating film 10, on the entire peripheral surface 13 of the rod 20 of the fishing rod 19, a coating liquid 14 containing filler particles 15 is applied to the rod 20 of the fishing rod 19, and then the peripheral surface 13 of the rod 20 of the fishing rod 19 is irradiated with ultraviolet light while irradiating with infrared light to heat the temperature of the peripheral surface 13 of the rod 20 to 400° C. or higher. An inorganic glass coating film 10a having an average thickness in the range of 0.5 μm or more and 20 μm or less is formed (deposited) on the peripheral surface 13 of the rod 20 of the fishing rod 19. The rod 20 of the fishing rod 19 on which the thin inorganic glass coating film 10a mainly composed of SiO2 as described above is formed (deposited) has an increased Young's modulus and is provided with high flexibility, impact resistance, water repellency, and antifouling and antirust effects. In addition, the inorganic glass coating film 10a has high film-forming properties and adhesion such that it is difficult for it to peel off even when the rod 20 is twisted or bent.

[0101] To form (form) an organic / inorganic hybrid glass coating film 10b, which is a glass-based coating film 10, on the entire peripheral surface 13 of the rod 20 of the fishing rod 19, the coating liquid 14 containing the filler particles 15 is applied to the rod 20 of the fishing rod 19, and then the peripheral surface 13 of the rod 20 is left at room temperature (normal temperature) without heating. Alternatively, after the coating liquid 14 is applied to the rod 20 of the fishing rod 19, the peripheral surface 13 of the rod 20 is irradiated with ultraviolet rays while being left at room temperature (normal temperature). Alternatively, after the coating liquid 14 is applied to the rod 20 of the fishing rod 19, the peripheral surface 13 of the rod 20 is irradiated with ultraviolet rays while being irradiated with infrared rays to heat the temperature of the peripheral surface 13 of the rod 20 to less than 400°C. An organic / inorganic hybrid glass coating film 10b having an average thickness in the range of 0.5 μm to 20 μm is formed (formed) on the peripheral surface 13 of the rod 20 of the fishing rod 19. The rod 20 of the fishing rod 19 on which the thin organic / inorganic hybrid glass coating film 10b mainly composed of SiO2 as described above is formed (deposited) has an increased Young's modulus and is provided with high flexibility, impact resistance, water repellency, antifouling and antirust effects, as well as high film-forming properties and adhesion such that the organic / inorganic hybrid glass coating film 10b is unlikely to peel off even when the rod 20 is twisted or bent.

[0102] If the average thickness of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) formed on the entire peripheral surface 13 of the rod 20 of the fishing rod 19 is less than 0.5 μm, the Young's modulus (GPa) of the glass-based coating film 10 cannot be increased, and the Young's modulus (GPa) of the rod 20 of the fishing rod 19 on which the glass-based coating film 10 is formed cannot be increased. In addition, the strength of the glass-based coating film 10 decreases, losing its protective function, and the peripheral surface 13 of the rod 20 cannot be sufficiently protected. If the average thickness of the glass-based coating film 10 formed on the entire peripheral surface 13 of the rod 20 of the fishing rod 19 exceeds 20 μm, the flexibility of the glass-based coating film 10 decreases, and the glass-based coating film 10 may peel off from the peripheral surface 13 of the rod 20 due to deformation (elastic deformation) of the rod 20.

[0103] Since the fishing rod 19 has an average thickness of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) within the above range, the Young's modulus (GPa) of the glass-based coating film 10 can be increased, and the Young's modulus (GPa) of the rod 20 on which the glass-based coating film 10 is formed can be increased. Even if the rod 20 is deformed (elastic deformation), the glass-based coating film 10 does not peel off from the peripheral surface 13 of the rod 20, and the fishing rod 19 can maintain the coated state of the glass-based coating film 10 by following the deformation of the rod 20, and can reliably protect the peripheral surface 13 of the rod 20, thereby preventing the peripheral surface 20 of the rod 19 from being scratched.

[0104] The filler particles 15 dispersed and mixed in the glass-based coating film 10 (the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b) formed on the entire peripheral surface 13 of the rod 20 of the fishing rod 19 have a Young's modulus (GPa) and a density (g / cm 3 ) is 30 or more. The Young's modulus (GPa) of the filler particles 15 is divided by its density (g / cm 3 ) is 30 or more, the Young's modulus (GPa) of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) made from the coating liquid 14 containing the filler particles 15 can be reliably increased, and the Young's modulus (GPa) of the rod 20 on which the glass-based coating film 10 is formed can be reliably increased.

[0105] The filler particles 15 dispersed and mixed in the glass-based coating film 10 (the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b) formed on the entire peripheral surface 13 of the rod 20 of the fishing rod 19 have an average particle diameter D 50 The average particle diameter D of the filler particles 15 is in the range of 0.1 μm or more and 20 μm or less. 50If the average particle diameter D of the filler particles 15 is less than 0.1 μm, the Young's modulus (GPa) of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) made from the coating liquid 14 containing the filler particles 15 cannot be increased, and the Young's modulus (GPa) of the rod 20 on which the glass-based coating film 10 is formed cannot be increased. 50 If the thickness exceeds 20 μm, the adhesion of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) to the peripheral surface 13 of the rod 20 of the fishing rod 19 will be significantly reduced, making it impossible to form a smooth glass-based coating film 10 on the peripheral surface 13 of the rod 20.

[0106] The fishing rod 19 has a filler particle 15 dispersed and mixed inside the glass-based coating film 10 (the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b) formed on the entire peripheral surface 13 of the rod 20. The filler particle 15 has an average particle diameter D 50 is in the above range, the Young's modulus (GPa) of the glass-based coating film 10 can be reliably increased, the Young's modulus (GPa) of the rod 20 on which the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) is formed can be reliably increased, and the glass-based coating film 10 has excellent adhesion to the peripheral surface 13 of the rod 20, so that a smooth glass-based coating film 10 can be formed on the peripheral surface 13 of the rod 20.

[0107] The filler particles 15 dispersed and mixed inside the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) formed on the entire peripheral surface 13 of the rod 20 of the fishing rod 19 have a content in the glass-based coating film 10 in the range of 5 to 50 volumes. If the content of the filler particles 14 is less than 5 volumes, the content of the filler particles 15 in the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) is small, and the Young's modulus (GPa) of the glass-based coating film 10 cannot be increased, and the Young's modulus (GPa) of the rod 20 on which the glass-based coating film 10 is formed cannot be increased. If the content of the filler particles 15 exceeds 50 volumes, the adhesion of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) to the peripheral surface 13 of the rod 20 is significantly reduced, and a smooth glass-based coating film 10 cannot be formed on the peripheral surface 13 of the rod 20.

[0108] In the fishing rod 19, the content of filler particles 15 dispersed and mixed inside the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) formed on the entire peripheral surface 13 of the rod 20 is within the above-mentioned range, so that the Young's modulus (GPa) of the glass-based coating film 10 can be reliably increased, and the Young's modulus (GPa) of the rod 20 on which the glass-based coating film 10 is formed can be reliably increased. In addition, the glass-based coating film 10 has excellent adhesion to the peripheral surface 13 of the rod 20, and a smooth glass-based coating film 10 can be formed on the peripheral surface 13 of the rod 20.

[0109] A fishing rod 19 has a glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) having a plurality of filler particles 15 dispersed and mixed therein formed over the entire peripheral surface 13 of a rod 20 (composite member 11). The filler particles 15 can improve the Young's modulus of the glass-based coating film 10, thereby improving the Young's modulus of the rod 20 on which the glass-based coating film 10 is formed.

[0110] The fishing rod 19 has a glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) having a plurality of filler particles 15 dispersed and mixed therein formed over the entire peripheral surface 13 of the rod 20 (composite member 11). This increases the Young's modulus of the rod 20, so that even if a large air resistance acts on the rod 29 when casting the fishing rod 19, the occurrence of vibration in the rod 20 during casting can be suppressed, and shaking of the rod 20 can be suppressed, the casting accuracy can be improved, and the flight direction of a lure or the like can be stabilized.

[0111] Fig. 10 is a perspective view of a propeller aircraft 28 shown as an example, and Fig. 11 is a cross-sectional view taken along line DD in Fig. 10. The above-mentioned glass-based coating film 10 (inorganic coating film 10a or organic / inorganic hybrid coating film 10b) is formed (coated) on the entire surface 13 (entire surface) of the propeller 21 of the propeller aircraft 28 (airplane) shown in Fig. 10.

[0112] The propeller 21 includes not only the propeller 21 used in a propeller plane 28 (airplane) carrying people, but also the propeller 21 used in a model aircraft (e.g., a radio-controlled model). The propeller 21 includes a fixed pitch propeller 21 in which the pitch of the blade is fixed, a selectable pitch propeller 21 (variable pitch propeller 21) in which the pitch can be switched between two stages, i.e., takeoff (low pitch) and cruising (high pitch), or multiple stages, and a constant speed (constant speed) propeller 21 in which the pitch is automatically adjusted and the rotation speed is selected. The material of the propeller 21 is fiber-reinforced plastic, but the propeller 21 may be a forged product of an aluminum alloy or a hollow steel blade. The propeller 21 is formed of a blade, a hub, an adapter, a spinner, and a spinner back plate. It is sufficient that the glass-based coating film 10 (the inorganic coating film 10a or the organic / inorganic hybrid coating film 10b) is formed on at least the entire surface 13 of the blade. The propeller 21 (blades) elastically deforms when the propeller aircraft 28 (flying object) is flying (when the propeller 21 (blades) are rotating).

[0113] The glass-based coating film 10 (inorganic coating film 10a or organic / inorganic hybrid coating film 10b) formed on the entire surface 13 of the propeller 21 is made from the above-mentioned coating liquid 14, which consists of a liquid organosilicon material (silicon material) consisting of at least one of organic polysilazane (polysilazane) and siloxane, an alkyl silicate condensate, and an inert organic solvent, and in which a plurality of plate-shaped filler particles 15 (at least one type of Si, SiO2, Al2O3, ZrO2, AlN, Si3N4, and SiC) have been mixed, or is made from the above-mentioned coating liquid 14, in which a plurality of plate-shaped filler particles 15 (at least one type of Si, SiO2, Al2O3, ZrO2, AlN, Si3N4, and SiC) have been mixed into a low molecular weight silane.

[0114] To form (deposit) the inorganic glass coating film 10a, which is the glass-based coating film 10, on the entire surface 13 of the propeller 21, the coating liquid 14 containing the filler particles 15 is applied to the propeller 21, and then the surface 13 of the propeller 21 is irradiated with ultraviolet light while irradiating with infrared light to heat the surface 13 of the propeller 21 to a temperature of 400°C or higher. The inorganic glass coating film 10a having an average thickness in the range of 0.5 μm to 20 μm is formed (deposited) on the surface 13 of the propeller 21. The propeller 21 on which the thin inorganic glass coating film 10a mainly composed of SiO2 described above is formed (deposited) has an increased Young's modulus, and has high flexibility, impact resistance, water repellency, and antifouling and antirust effects, as well as high film formability and adhesion such that the inorganic glass coating film 10a is not easily peeled off even when the propeller 21 is twisted or bent.

[0115] To form (form) an organic / inorganic hybrid glass coating film 10b, which is a glass-based coating film 10, on the entire surface 13 of the propeller 21, a coating liquid 14 containing filler particles 15 is applied to the propeller 21, and then the surface 13 of the propeller 21 is left at room temperature (normal temperature) without heating. Alternatively, after the coating liquid 14 is applied to the propeller 21, the surface 13 of the propeller 21 is irradiated with ultraviolet rays while being left at room temperature (normal temperature). Alternatively, after the coating liquid 14 is applied to the propeller 21, the surface 13 of the propeller 21 is irradiated with ultraviolet rays while being irradiated with infrared rays to heat the temperature of the surface 13 of the propeller 21 to less than 400°C. An organic / inorganic hybrid glass coating film 10b having an average thickness in the range of 0.5 μm to 20 μm is formed (formed) on the surface 13 of the propeller 21. The propeller 21 on which the thin organic / inorganic hybrid glass coating film 10b, which is mainly composed of SiO2 as described above, is formed (deposited) has an increased Young's modulus and is provided with high flexibility, impact resistance, water repellency, and anti-fouling and anti-rust effects. In addition, the propeller 21 has high film-forming properties and adhesion such that the organic / inorganic hybrid glass coating film 10b is not easily peeled off even when the propeller 21 is twisted or bent.

[0116] If the average thickness of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) formed on the entire surface 13 of the propeller 21 is less than 0.5 μm, the Young's modulus (GPa) of the glass-based coating film 10 cannot be increased, and the Young's modulus (GPa) of the propeller 21 on which the glass-based coating film 10 is formed cannot be increased. In addition, the strength of the glass-based coating film 10 decreases, causing it to lose its protective function, and it is not possible to adequately protect the surface 13 of the propeller 21. If the average thickness of the glass-based coating film 10 formed on the entire surface 13 of the propeller 21 exceeds 20 μm, the flexibility of the glass-based coating film 10 decreases, and the glass-based coating film 10 may peel off from the surface 13 of the propeller 21 due to deformation (elastic deformation) of the propeller 21.

[0117] Since the average film thickness of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) of the propeller 21 is within the above range, the Young's modulus (GPa) of the glass-based coating film 10 can be increased, and the Young's modulus (GPa) of the propeller 21 on which the glass-based coating film 10 is formed can be increased. Even if the propeller 21 is deformed (elastic deformation), the glass-based coating film 10 does not peel off from the surface 13 of the propeller 21, and can maintain the coated state of the glass-based coating film 10 by following the deformation of the propeller 21, and can reliably protect the surface 13 of the propeller 21, thereby preventing the surface 13 of the propeller 21 from being scratched.

[0118] The filler particles 15 dispersed and mixed in the glass-based coating film 10 (the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b) formed on the entire surface 13 of the propeller 21 have a Young's modulus (GPa) and a density (g / cm 3 ) is 30 or more. The propeller 21 is a filler particle 15 having a Young's modulus (GPa) divided by its density (g / cm 3) is 30 or more, it is possible to reliably increase the Young's modulus (GPa) of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) made from the coating liquid 14 containing the filler particles 15, and it is possible to reliably increase the Young's modulus (GPa) of the propeller 21 on which the glass-based coating film 10 is formed.

[0119] The filler particles 15 dispersed and mixed in the glass-based coating film 10 (the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b) formed on the entire surface 13 of the propeller 21 have an average particle diameter D 50 The average particle diameter D of the filler particles 15 is in the range of 0.1 μm or more and 20 μm or less. 50 If the average particle diameter D of the filler particles 15 is less than 0.1 μm, the Young's modulus (GPa) of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) made from the coating liquid 14 containing the filler particles 15 cannot be increased, and the Young's modulus (GPa) of the propeller 21 on which the glass-based coating film 10 is formed cannot be increased. 50 If the thickness exceeds 20 μm, the adhesion of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) to the surface 13 of the propeller 21 will be significantly reduced, making it impossible to form a smooth glass-based coating film 10 on the surface 13 of the propeller 21.

[0120] The propeller 21 has an average particle size D of the filler particles 15 dispersed and mixed inside the glass-based coating film 10 (the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b) formed on the entire surface 13 of the propeller 21. 50is in the above range, the Young's modulus (GPa) of the glass-based coating film 10 can be reliably increased, the Young's modulus (GPa) of the propeller 21 on which the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) is formed can be reliably increased, and the glass-based coating film 10 has excellent adhesion to the surface 13 of the propeller 21, making it possible to form a smooth glass-based coating film 10 on the surface 13 of the propeller 21.

[0121] The filler particles 15 dispersed and mixed inside the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) formed on the entire surface 13 of the propeller 21 have a content in the glass-based coating film 10 in the range of 5 to 50 volumes. If the content of the filler particles 15 is less than 5 volumes, the content of the filler particles 15 in the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) is small, and the Young's modulus (GPa) of the glass-based coating film 10 cannot be increased, and the Young's modulus (GPa) of the propeller 21 on which the glass-based coating film 10 is formed cannot be increased. If the content of the filler particles 15 exceeds 50 volumes, the adhesion of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) to the surface 13 of the propeller 21 is significantly reduced, and a smooth glass-based coating film 10 cannot be formed on the surface 13 of the propeller 21.

[0122] Since the content of filler particles 15 dispersed and mixed inside the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) formed over the entire surface 13 of the propeller 21 is within the above-mentioned range, the Young's modulus (GPa) of the glass-based coating film 10 can be reliably increased, and the Young's modulus (GPa) of the propeller 21 on which the glass-based coating film 10 is formed can be reliably increased. In addition, the glass-based coating film 10 has excellent adhesion to the surface 13 of the propeller 21, and a smooth glass-based coating film 10 can be formed on the surface 13 of the propeller 21.

[0123] A propeller plane 28 (flying object) using a propeller 21 (composite material 11) has a glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) having a plurality of filler particles 15 dispersed and mixed therein formed over the entire surface 13 of the propeller 21 (composite material 11), and the filler particles 15 can improve the Young's modulus of the glass-based coating film 10, thereby improving the Young's modulus of the propeller 21 on which the glass-based coating film 10 is formed.

[0124] A propeller plane 28 (flying object) using a propeller 21 (composite member 11) can increase the Young's modulus of the propeller 21 by forming a glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) having a plurality of filler particles 15 dispersed and mixed therein over the entire surface 13, so that even if a large air resistance acts on the propeller 21 during the flight of the propeller plane 28 (flying object) using the propeller 21, the occurrence of vibration in the propeller 21 during the flight of the propeller plane 28 can be suppressed, and the propulsive force of the propeller 21 can be improved. Since the occurrence of vibration in the propeller 21 is suppressed and the propulsive force of the propeller 21 is improved, the flight speed of the propeller plane 28 (flying object) can be increased, and the stability of the propeller plane 28 during flight can be improved. A propeller aircraft 28 (flying object) can reduce noise generated from the propeller 21 during flight.

[0125] Fig. 12 is a perspective view of a helicopter 29 shown as an example, and Fig. 13 is a cross-sectional view taken along line EE of Fig. 12. The entire surface 13 of the rotor 22 of the helicopter 29 shown in Fig. 12 is formed (coated) with the above-mentioned glass-based coating film 10 (inorganic coating film 10a or organic / inorganic hybrid coating film 10b).

[0126] The rotor 22 includes not only the rotor 22 used in a helicopter 29 (flying object) carrying people, but also the rotor 22 used in a model helicopter (e.g., a radio-controlled model), and the rotor 22 used in a drone (flying object). Furthermore, not only the main rotor but also the tail rotor is included.

[0127] The rotor 22 may be a tandem rotor, in which two horizontally rotating main rotors are arranged one behind the other without using an anti-torque tail rotor, and two or more large horizontal rotors rotate in opposite directions to cancel the torque effect on the aircraft, a coaxial counter-rotating rotor, in which two rotors are mounted one above the other on the same axis without using an anti-torque tail rotor, and the rotors rotate in opposite directions to cancel the torque effect on the aircraft, a crossed twin rotor, in which two rotors rotating in opposite directions are combined and rotated in opposite directions to cancel the torque effect on the aircraft without using an anti-torque tail rotor, a side-by-side rotor, in which the rotors are attached to the tips of wings or outriggers extending at right angles from the aircraft, and a multi-rotor, in which four rotors are arranged in an X-shape at the left front, right front, left rear, and right rear. The rotor 22 is made of a glass fiber composite material, but the rotor 22 may be made of an aluminum alloy. The rotor 22 (blades) elastically deforms when a helicopter 29 (flying object) or a drone (flying object) is flying and hovering (when the rotor (blades) are rotating).

[0128] The glass-based coating film 10 (inorganic coating film 10a or organic / inorganic hybrid coating film 10b) formed on the entire surface 13 of the rotor 22 is made from the above-mentioned coating liquid 14, which consists of a liquid organosilicon material (silicon material) consisting of at least one of organic polysilazane (polysilazane) and siloxane, an alkyl silicate condensate, and an inert organic solvent, and in which a plurality of plate-shaped filler particles 15 (at least one type of Si, SiO2, Al2O3, ZrO2, AlN, Si3N4, and SiC) have been mixed, or is made from the above-mentioned coating liquid 14, in which a plurality of plate-shaped filler particles 15 (at least one type of Si, SiO2, Al2O3, ZrO2, AlN, Si3N4, and SiC) have been mixed into a low molecular weight silane.

[0129] To form (deposit) the inorganic glass coating film 10a, which is the glass-based coating film 10, on the entire surface 13 of the rotor 22, a coating liquid 14 containing filler particles 15 is applied to the rotor 22, and then the surface 13 of the rotor 22 is irradiated with ultraviolet light while irradiating with infrared light to heat the surface 13 of the rotor 22 to 400°C or higher. An inorganic glass coating film 10a having an average thickness in the range of 0.5 μm to 20 μm is formed (deposited) on the surface 13 of the rotor 22. The rotor 22 on which the thin inorganic glass coating film 10a mainly composed of SiO2 described above is formed (deposited) has an increased Young's modulus, and has high flexibility, impact resistance, water repellency, and antifouling and antirust effects, as well as high film-forming properties and adhesion such that the inorganic glass coating film 10a is not easily peeled off even when the rotor 22 is twisted or bent.

[0130] To form (deposit) an organic / inorganic hybrid glass coating film 10b, which is a glass-based coating film 10, on the entire surface 13 of the rotor 22, a coating liquid 14 containing filler particles 15 is applied to the rotor 22, and then the surface 13 of the rotor 22 is left at room temperature (normal temperature) without heating. Alternatively, after applying the coating liquid 14 to the rotor 22, the surface 13 of the rotor 22 is irradiated with ultraviolet light while being left at room temperature (normal temperature). Alternatively, after applying the coating liquid 14 to the rotor 22, the surface 13 of the rotor 22 is irradiated with infrared light while being irradiated with ultraviolet light to heat the surface 13 of the rotor 22 to a temperature of less than 400°C. An organic / inorganic hybrid glass coating film 10b having an average thickness in the range of 0.5 μm to 20 μm is formed (deposited) on the surface 13 of the rotor 22. The rotor 22 on which the thin organic / inorganic hybrid glass coating film 10b, which is mainly composed of SiO2 as described above, is formed (deposited) has an increased Young's modulus and is provided with high flexibility, impact resistance, water repellency, and anti-fouling and anti-rust effects. In addition, the rotor 22 has high film-forming properties and adhesion such that the organic / inorganic hybrid glass coating film 10b is not easily peeled off even when the rotor 22 is twisted or bent.

[0131] If the average thickness of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) formed on the entire surface 13 of the rotor 22 is less than 0.5 μm, the Young's modulus (GPa) of the glass-based coating film 10 cannot be increased, and the Young's modulus (GPa) of the rotor 22 on which the glass-based coating film 10 is formed cannot be increased. In addition, the strength of the glass-based coating film 10 decreases, losing its protective function, and the surface 13 of the rotor 22 cannot be sufficiently protected. If the average thickness of the glass-based coating film 10 formed on the entire surface 13 of the rotor 22 exceeds 20 μm, the flexibility of the glass-based coating film 10 decreases, and the glass-based coating film 10 may peel off from the surface 13 of the rotor 22 due to deformation (elastic deformation) of the rotor 22.

[0132] Since the average thickness of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) of the rotor 22 is within the above range, the Young's modulus (GPa) of the glass-based coating film 10 can be increased, and the Young's modulus (GPa) of the rotor 22 on which the glass-based coating film 10 is formed can be increased. Even if the rotor 22 is deformed (elastically deformed), the glass-based coating film 10 does not peel off from the surface 13 of the rotor 22, and can maintain the coated state of the glass-based coating film 10 by following the deformation of the rotor 22, and can reliably protect the surface 13 of the rotor 22, thereby preventing the surface 13 of the rotor 22 from being scratched.

[0133] The filler particles 15 dispersed and mixed in the glass-based coating film 10 (the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b) formed on the entire surface 13 of the rotor 22 have a Young's modulus (GPa) and a density (g / cm 3 The rotor 22 divides the Young's modulus (GPa) of the filler particles 15 by its density (g / cm 3) is 30 or more, the Young's modulus (GPa) of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) made from the coating liquid 14 containing the filler particles 15 can be reliably increased, and the Young's modulus (GPa) of the rotor 22 on which the glass-based coating film 10 is formed can be reliably increased.

[0134] The filler particles 15 dispersed and mixed in the glass-based coating film 10 (the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b) formed on the entire surface 13 of the rotor 22 have an average particle diameter D 50 The average particle diameter D of the filler particles 15 is in the range of 0.1 μm or more and 20 μm or less. 50 If the average particle diameter D of the filler particles 15 is less than 0.1 μm, the Young's modulus (GPa) of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) made from the coating liquid 14 containing the filler particles 15 cannot be increased, and the Young's modulus (GPa) of the rotor 22 on which the glass-based coating film 10 is formed cannot be increased. 50 If the thickness exceeds 20 μm, the adhesion of the glass-based coating film 10 (inorganic glass coating film 10 a or organic / inorganic hybrid glass coating film 10 b) to the surface 13 of the rotor 22 will be significantly reduced, making it impossible to form a smooth glass-based coating film 10 on the surface 13 of the rotor 22.

[0135] The rotor 22 has a mean particle size D of the filler particles 15 dispersed and mixed inside the glass-based coating film 10 (the inorganic glass coating film 10a or the organic / inorganic hybrid glass coating film 10b) formed on the entire surface 13 of the rotor 22. 50is in the above range, the Young's modulus (GPa) of the glass-based coating film 10 can be reliably increased, the Young's modulus (GPa) of the rotor 22 on which the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) is formed can be reliably increased, and the glass-based coating film 10 has excellent adhesion to the surface 13 of the rotor 22, and a smooth glass-based coating film 10 can be formed on the surface 13 of the rotor 22.

[0136] The filler particles 15 dispersed and mixed inside the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) formed on the entire surface 13 of the rotor 22 have a content in the glass-based coating film 10 in the range of 5 to 50 volumes. If the content of the filler particles 15 is less than 5 volumes, the content of the filler particles 15 in the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) is small, and the Young's modulus (GPa) of the glass-based coating film 10 cannot be increased, and the Young's modulus (GPa) of the rotor 22 on which the glass-based coating film 10 is formed cannot be increased. If the content of the filler particles 15 exceeds 50 volumes, the adhesion of the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) to the surface 13 of the rotor 22 is significantly reduced, and a smooth glass-based coating film 10 cannot be formed on the surface 13 of the rotor 22.

[0137] Since the content of filler particles 15 dispersed and mixed inside the glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) formed on the entire surface 13 of the rotor 22 is within the above-mentioned range, the Young's modulus (GPa) of the glass-based coating film 10 can be reliably increased, the Young's modulus (GPa) of the rotor 22 on which the glass-based coating film 10 is formed can be reliably increased, and the glass-based coating film 10 has excellent adhesion to the surface 13 of the rotor 22, and a smooth glass-based coating film 10 can be formed on the surface 13 of the rotor 22.

[0138] In a helicopter 29 (flying object) or drone (flying object) using a rotor 22 (composite material 11), a glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) having a plurality of filler particles 15 dispersed and mixed therein is formed over the entire surface 13 of the rotor 22 (composite material 11), and the filler particles 15 can improve the Young's modulus of the glass-based coating film 10, thereby improving the Young's modulus of the rotor 22 on which the glass-based coating film 10 is formed.

[0139] A helicopter 29 (flying object) or drone (flying object) using a rotor 22 (composite material 11) can have a high Young's modulus of the rotor 22 by forming a glass-based coating film 10 (inorganic glass coating film 10a or organic / inorganic hybrid glass coating film 10b) having a plurality of filler particles 15 dispersed and mixed therein over the entire surface 13. Therefore, even if a large air resistance acts on the rotor 22 when the helicopter 29 (flying object) or drone (flying object) using the rotor 22 is flying or hovering, the occurrence of vibration in the rotor 22 when the helicopter 29 or drone is flying or hovering can be suppressed, and the propulsive force of the rotor 22 can be improved.

[0140] In the helicopter 29 (flying object) or drone (flying object), the generation of vibrations in the rotor 22 is suppressed and the propulsive force of the rotor 22 is improved, so that the flight speed of the helicopter 29 (flying object) or drone (flying object) can be increased and the stability during flight of the helicopter 29 or drone can be improved. The helicopter 29 (flying object) or drone (flying object) can reduce noise generated from the rotor 22 during flight or hovering. [Explanation of symbols]

[0141] 10 Glass-based coating film 10a Inorganic glass coating film 10b Organic / inorganic hybrid glass coating film 11 Composite Materials 12 Lightweight substrate 13 surfaces (surface, circumferential surface) 14 Coating fluid 15 Filler particles 16. Golf Clubs 17 Club Head 18 Shaft 19 Fishing Rod 20 Rod 21 Propeller 22 rotor 23 Surface layer 24 Covering layer 25 Back layer 26 Middle Class 27 Anchor section 28 Propeller plane (flying object) 29 Helicopter (Flying object)

Claims

1. The present invention comprises an elastically deformable lightweight substrate and a glass-based coating film formed on the lightweight substrate and having a plurality of filler particles dispersed therein; The density of the lightweight substrate is 3.0 g / cm 3 The Young's modulus (GPa) of the filler particles is less than or equal to the density (g / cm 3 ) is 30 or more.

2. 2. The composite member according to claim 1, wherein the lightweight base material is any one of CFRP, FRP, ABS resin, polycarbonate, carbon fiber polycarbonate, aluminum alloy (Al alloy), and magnesium alloy (Mg alloy).

3. 3. The composite material according to claim 1, wherein the average thickness of the glass-based coating film is from 0.5 μm to 20 μm.

4. The filler particles are Si, SiO 2 , Al 2 O 3 , ZrO 2 , AlN, Si 3 N 4 4. The composite member according to claim 1, wherein the composite member is made of at least one of the following materials: SiC, SiO2, or SiC.

5. The composite member according to claim 4 , wherein the filler particles have a plate-like shape.

6. The average particle size D of the filler particles 50 The composite material according to claim 5, wherein the thickness is 0.1 μm or more and 20 μm or less.

7. 7. The composite member according to claim 6, wherein the content of the filler particles in the glass-based coating film is 5 to 50 volume %.

8. 8. The composite member according to claim 7, wherein the glass-based coating film is either a glass-based inorganic coating film or a glass-based organic / inorganic hybrid coating film.

9. 9. A golf club, comprising a shaft made of the composite material according to claim 1.

10. A fishing rod, comprising the composite member according to any one of claims 1 to 8.

11. 9. A flying object, comprising a propeller or rotor made of the composite material according to claim 1.

Citation Information

Patent Citations

  • Golf club

    JP2019051291A

  • Coating liquid and coating method

    JP2021014514A